Dendritic cells and the initiation of contact sensitivity to fluorescein isothiocyanate. - Macatonia, S E (1986)
Lymph node cells taken 24 hr after skin-painting mice with the contact sensitizer fluorescein isothiocyanate (FITC) induce delayed-type hypersensitivity in recipient mice. Skin-painting increased the number of dendritic cells (DC) in the draining lymph nodes without significantly changing the number of lymphocytes at 24 hr. The antigen was preferentially located on the DC. Raising the dose of FITC increased both the number of DC and the amount per cell. The addition of these DC to syngeneic lymph node cells at a ratio as low as 1:300 initiated proliferative responses in vitro. The level of proliferation was related to the amount of antigen on the DC. Mice given 50,000 of these fluorescent DC developed specific contact sensitivity reactions. DC exposed in vitro to FITC also acquired antigen and were able to initiate proliferative responses in vitro and to sensitize recipient mice. The DC may therefore be the prime cell involved in the induction of delayed-type hypersensitivity.